Characterization of solid fuel by pome: article - Mohd Shah, Muhammad Najmi; Ku Hamid, Ku Halim (2019)
The palm oil industry is recognized as one of the major agriculture contributions to the abundant production of oil palm solid wastes. Hence, this study is aimed at investigating the solid fuel characterization of Palm Oil Mill Effluent (POME) using Thermogravimetric analysis (TGA). The heating value (HHV), ultimate and proximate analysis was determined using standard ASTM techniques. Consequently, the thermal decomposition behavior of the fuel was determined by heating the sample from 50°C to 900°C in a thermogravimetric analyzer (TGA) at 10°C per min heating rate. The ultimate and proximate analysis revealed that POME powder contains low moisture content, ash content and high fixed carbon, volatile matter content while the HHV was 17.57 MJ/kg. In addition, TGA results indicated thermal decomposition of the fuel occurs in four stages. Devolatilization commenced at 206°C with a peak devolatilization temperature (Tmax) of 400°C respectively resulting in 80% weight loss. From Fourier Transform InfraRed Spectroscopic (FTIR), it shows the major functional group in solid POME which was alcohol, hexanoic acids, butyraldehyde, alkenes group, and alkyl halides. As a conclusion, solid POME is suitable to be used as solid fuel because it is environmentally friendly